NLFEA of precast concrete slab for housing / [cakera padat] - 249504 Goh, Lyn Dee (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Engineering (Civil - Structure)) - Universiti Teknologi Malaysia, 2004